2014
DOI: 10.1111/bjd.13052
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anatomical locations of cutaneous melanoma in men and women: a population‐based study inFrance

Abstract: Sex differences in occupational and leisure time ultraviolet exposure, clothing (including shoes), hairstyle, and side and photo exposure in cars could explain these results. General preventive messages could be completed by sex-specific advice for melanoma prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
3
21
1
4
Order By: Relevance
“…A recent study from France reported a similar trend. 16 Overall, these data support the hypothesis that women are diagnosed with melanomas on the lower legs and arms at a higher frequency than men. The differences in melanoma location between the sexes may reflect their different clothing and sun-protective measures.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study from France reported a similar trend. 16 Overall, these data support the hypothesis that women are diagnosed with melanomas on the lower legs and arms at a higher frequency than men. The differences in melanoma location between the sexes may reflect their different clothing and sun-protective measures.…”
Section: Discussionsupporting
confidence: 70%
“…Although prior studies on male pattern baldness and risk of skin cancer were sparse, there was anecdotal impression in clinics that balding may be a risk factor for both melanoma and KC in scalp compared with non‐balding, with the perception of delayed detection due to concealment from hair coverage, as well as the protection against sun damage to scalp by hair coverage in non‐balding men. Studies have also linked hair cover and hairstyle to anatomic distribution of melanoma . One clinical cross‐sectional study found a significant association between male pattern baldness and both melanoma and KC of the scalp .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies on male pattern baldness and risk of skin cancer were sparse, with some clinical evidence reporting that skin cancer of the scalp occurs more frequently in balding man . Prior literatures have also proposed that the long‐term protective role of hair cover may reduce UV exposure and may be associated with the higher incidence of head and neck melanomas in men than in women, as reviewed before …”
mentioning
confidence: 99%
“…Patients, through self-screening, can be the first to detect suspicious skin lesions (Rigel et al, 2010). As women pay particular attention to the health of their skin, especially the face and extremities that are the most common anatomical sites of skin cancer manifestation, they have a greater probability of self-detecting skin anomalies (Chevalier et al, 2014, Lee et al, 2014). Women tend to be more open and communicative about voicing their health concerns, and throughout their lives tend to have more contact with health professionals.…”
Section: Detection and Treatmentmentioning
confidence: 99%